A Simulation of a Tsunami Model Using Geographical Information Systems. - Hans Christian Ang, C; Cubero,Cliff Anthony; Cunanan, Katrina Corazon; Nishimori, Kent.; Chua, Caslon
Tsunamis can sometimes be more destructive than the earthquake that caused them. Damage from a tsunami comes not only from the tsunami wave itself, but also the rapid retreat of water prior to arrival of the tsunami wave and the debris carried by the tsunami wave add to the destructive potential. In addition, ñres started by the preceding earthquake are often spread by the tsunami waves. Researches are now being made in the studies for its behavior. This project worked on creating a Geographical Information System that could represent a tsunami model with regards to the calculating the extent of damage and other specifications to aid in the study of tsunamis. In particular, it implementswavemodelling and other related models to simulate a tsunami on the area of Talin Bay.
Keywords: Tsunami model; Geographical Information Systems (GIS).; Tsunami, Earthquake, Modeling, Simulation